Effect of Continuous Glucose Monitoring on Hypoglycemia in Type 1 Diabetes - Battelino, Tadej; Phillip, Moshe; Bratina, Natasa; Nimri, Revital; Oskarsson, Per; Bolinder, Jan (Diabetes care, 2011)
OBJECTIVE: To assess the impact of continuous glucose monitoring on hypoglycemia in people with type 1 diabetes. RESEARCH DESIGN AND METHODS: In this randomized, controlled, multicenter study, 120 children and adults on intensive therapy for type 1 diabetes and a screening level of glycated hemoglobin A₁c (HbA₁c) <7.5% were randomly assigned to a control group performing conventional home monitoring with a blood glucose meter and wearing a masked continuous glucose monitor every second week for five days or to a group with real-time continuous glucose monitoring. The primary outcome was the time spent in hypoglycemia (interstitial glucose concentration <63 mg/dL) over a period of 26 weeks. Analysis was by intention to treat for all randomized patients. RESULTS: The time per day spent in hypoglycemia was significantly shorter in the continuous monitoring group than in the control group (mean ± SD 0.48 ± 0.57 and 0.97 ± 1.55 h/day, respectively; ratio of means 0.49; 95% CI 0.26-0.76; P = 0.03). HbA₁c at 26 weeks was lower in the continuous monitoring group than in the control group (difference -0.27%; 95% CI -0.47 to -0.07; P = 0.008). Time spent in 70 to 180 mg/dL normoglycemia was significantly longer in the continuous glucose monitoring group compared with the control group (mean hours per day, 17.6 vs. 16.0, P = 0.009). CONCLUSIONS: Continuous glucose monitoring was associated with reduced time spent in hypoglycemia and a concomitant decrease in HbA₁c in children and adults with type 1 diabetes.